AUDIT DELAY DAN TIMELINESS AUDIT DELAY AND TIMELINESS (Students' Journal of Accounting and Banking, 2012)
This study is a study that examined the financial leverage ratio and liquidity, ownership structure and institutional ownership is public ownership, as well as the auditor's opinion, and the size of the KAP of audit delay and timeliness. Signal in accordance with the theory that an action taken by management to provide guidance to investors about how the management of the company's prospects look, with a signal - a signal success or failure of management (agent) who presented to the owner (principal).Based on the theory that the signal to see a signal - a signal success or failure of the company, the company tried to publish financial statements have been audited to the public in an accurate and timely. In this study, this study used a purposive sampling and obtain samples of 278 samples of the company. By using multiple regression analysis and logistic regression to explain the relationship between these variables.The test results show that the t statistic leverage, liquidity, institutional ownership, public ownership, the auditor's opinion, and does not affect the size of the KAP audit delay. Firm size is only just acquired a significant effect on the timeliness, while leverage, liquidity, institutional ownership, public ownership and auditor's opinion does not affect the timeliness.Keywords: audit delay, timeliness, leverage, liquidity, institutional ownership, public ownership, auditor's opinion, and the size of the KAP.